2020
DOI: 10.30994/sjik.v9i2.321
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Analysis of Musculoskeletal Disorders in Pottery Making Workers in Kasongan, Bantul

Abstract: Musculoskeletal problems are problematic in Indonesia because manual work activities such as lifting, transporting, pulling and pushing are still being done. Pottery-making workers in the Kasongan are still doing those moves traditionally such as lifting, transporting, pulling and pushing manually. The purpose of this study was to analyze the risk of MSDs in the pottery making workers in Kasongan. This research was cross sectional design. The sample amounted to 78 workers selected using accidental sampling tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(8 reference statements)
1
0
0
Order By: Relevance
“…The Chi-Square test calculations Between age and symptoms of musculoskeletal disorders, it was found that the p-value was <0.05 (0.039 <0.05), this means that there was a significant relationship between age and complaints of musculoskeletal disorders. This is in line with research [2] states that there is a relationship between age and symptoms of musculoskeletal disorders.…”
Section: Age Factorsupporting
confidence: 91%
“…The Chi-Square test calculations Between age and symptoms of musculoskeletal disorders, it was found that the p-value was <0.05 (0.039 <0.05), this means that there was a significant relationship between age and complaints of musculoskeletal disorders. This is in line with research [2] states that there is a relationship between age and symptoms of musculoskeletal disorders.…”
Section: Age Factorsupporting
confidence: 91%